Urban dynamics; An impression of Surabaya's sociolinguistic setting - Hoogervorst, Tom G. (Wacana, Journal of the Humanities of Indonesia, 2009)
This paper examines the sociolinguistic situation in the city of Surabaya, by presenting an impression of various phenomena unique to Indonesia's second largest city. A surprisingly little amount of linguistic research has heretofore been carried out on this subject, whereas it transpires from this study that enough intriguing and unique things can be found in this Southeast Asian metropolis, both among its Javanese majority as well as its Madurese and Chinese inhabitants. Due to the lack of earlier relevant publications, this research is largely based on the results of several fieldwork trips, which included the pleasant activities of watching television, interviewing people and making excursions in and around Surabaya to experience how languages are used in daily life. Additionally, concepts such as "language mixing", "slang" and "attitudes towards language" are involved and considered very significant in disentangling the role and function of language in an urban setting.